ANALISIS KESALAHAN BERBAHASA PADA BERITA DI MEDIA ONLINE “FACEBOOK DAN INSTAGRAM” - wa mirna; Syaidah Syaidah (LP2M UIN Abdul Muthalib Sangadji Ambon, 2022)
ABSTRACTThis study aims to describe (1) phonological, morphological, syntactic, and semantic errors found in the Indonesian discourse on the Humanitarian Crisis and the Death of the Democratic Space under President Joko Widodo's leadership which was published by the Papuan Student Alliance-AMP on March 14, 2022 through the media. Facebook online, (2) phonological, morphological, syntactic, and semantic errors contained in the discourse